Thick branes in the scalar–tensor representation of f(R, T) gravity - João Luís Rosa (SpringerOpen, 2021)
Abstract Braneworld scenarios consider our observable universe as a brane embedded in a five-dimensional bulk. In this work, we consider thick braneworld systems in the recently proposed dynamically equivalent scalar–tensor representation of f(R, T) gravity, where R is the Ricci scalar and T the trace of the stress–energy tensor. In the general $$f\left( R,T\right) $$ f R , T case we consider two different models: a brane model without matter fields where the geometry is supported solely by the gravitational fields, and a second model where matter is described by a scalar field with a potential. The particular cases for which the function $$f\left( R,T\right) $$ f R , T is separable in the forms $$F\left( R\right) +T$$ F R + T and $$R+G\left( T\right) $$ R + G T , which give rise to scalar–tensor representations with a single auxiliary scalar field, are studied separately. The stability of the gravitational sector is investigated and the models are shown to be stable against small perturbations of the metric. Furthermore, we show that in the $$f\left( R,T\right) $$ f R , T model in the presence of an extra matter field, the shape of the graviton zero-mode develops internal structure under appropriate choices of the parameters of the model.